Development of timber concrete composite (TCC) beam with post-tensioning - Obeed, Wissam Mushina (2020)
Post-tensioning is a method of reinforcing (strengthening) concrete or other materials with high-strength steel strands or bars. The timber type that is used in all researches is the engineering timber products laminated veneer lumber (LVL) and glue-laminated wood (Glu-Lam), while avoiding using natural timber due to its properties’ variety. More recent improvement is using post-tensioning technique for the engineering timber products. The main material in this research is natural Kempas timber. The primary objective of this research is to develop of a method of timber beam post-tensioning and proposed empirical Equation to predict the bending moment capacity for timber beam and timber concrete composite beam through the bending strength properties. The experimental program is divided into 3 major phases across the duration of this study. Phase A present post-tensioning method, this phase indicate two methods of posttensioning “forced bending jacking PT-B” and “pre-stressing jacking PT-J”. Phase B present timber bending performance in term of (strength and failure behavior), include 4 point bending tests for timber beams and post-tensioning timber beams, the timber beam size (40 mm x90 mm x1200 mm) the tendon type is threaded rod bar with two colors silver color (9.4 mm) and black color (8.85 mm) . Phase C involved post-tensioned timber concrete composite beam (the concrete layer is 65 mm) Bending Performance. From the test results for the two methods of pre-stressing it is clear that pre-stressing Jacking give higher residual deflection 98.2 % for silver color rod bar against black color with 88.8 % residual deflection. So this type of rod bar (silver color with long nut coupling) is the more efficient in use due to the high contact friction surface area for long coupling nut. The bending tests of post-tensioned beams show the range of bending strength capacity increasing 12 % to 46 %. There were three types of failure is tensile, compression and splitting shear failure depending on the timber quality (degree of natural effect). The PT-TCC give bending strength increment according to degree of composite action 500 mm, 100 mm and 70 mm screw spacing is 68 %, 85 % and 150 % respectively. The empirical Equation derived for bending moment capacity for posttensioning Kempas timber beam is basically depended on the experimental relation between vertical deflection and rod bar strain. The empirical Equation shows 3.06 kNvi constant difference for the theoretical equation and the equation form is PTempirical = 8EI∆ eL2 − 3.06. In the case of PT-TCC the proposed equation depend on the concept of connector slip modulus. A three paths of estimation were discussed depend on push out test slip modulus. The gamma design method show that the slip modulus of pushout test gives a proper estimation in the case of PT-TCC specimens bending strength design.